A surface carbonization strategy towards MoS2 microspheres with enhanced electrochemical hydrogen evolution activity. (3rd June 2019) - Fei, Chengwei; Cui, Lixia; Du, Haiwei; Gu, Lina; Xu, Gengsheng; Yuan, Yupeng
Abstract : Decorating N-doped carbon nanoparticles on MoS2 via a surface carbonization strategy to boost electrocatalytic hydrogen generation. Abstract : Surface engineering is of great importance to rationally change the catalyst's surface structure and provide insights into the surface reactivity when developing high-efficiency and earth-abundant catalysts for electrocatalytic water splitting. Herein, nitrogen-doped carbon (NC) nanoparticle-decorated MoS2 is successfully constructed via a surface carbonization strategy simply by sintering MoS2 microspheres and dicyandiamide (DCDA), which generates tiny NC nanoparticles on the MoS2 surface. The presence of NC nanoparticles on MoS2 not only facilitates the charge transfer and reaction kinetics but also promotes the hydrogen adsorption during the electrocatalytic hydrogen evolution reaction (HER) process, thereby endowing the catalyst with a much lower overpotential and a higher current density in comparison to pristine MoS2 . This work indicates that the surface carbonization strategy provides a promising way for designing highly active electrocatalysts in terms of surface structure engineering.